Development of Nature-Based Practical Instructions to Improve Science Process Skills in Class XI MIA Acid-Base Material - Sili, Jeniana Uba; Kurniasih, Yeti; Nufida, Baiq Asma; Khery, Yusran (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
practicum manuals available so students only used practicum guides from textbooks. This causes ineffective practicum activities which have an impact on students' low science process skills.The aim of this research is to develop nature-based practicum instructions, and determine the characteristics and feasibility of practicum instructions, as well as determine student responses to the practicum instructions developed. The research method used is Research and Development or R&D with the 4D development model (define, design, develop, disseminate). Data collection techniques use observation sheets and questionnaires. The research results obtained an average value from the validation of the expert team, namely 87.69% with very feasible criteria. Validation results from practitioners obtained an average of 96% with very feasible criteria. The results of the student questionnaire responses obtained an average of 82.75% with very feasible criteria and the results of observations of science process skills obtained an average of above 75% for each aspect with very feasible criteria. It can be concluded that the nature-based practical instructions that have been developed still need to be carried out in the next stage and are very suitable for use in experiments.